Analisa Proses Annealing Dengan Hasil Pengelasan Terhadap Sifat Mekanik Baja Karbon Rendah - Rasyidi Rasyidi (MAJALAH TEKNIK SIMES, 2018)
The heat treatment process provided on a metal or alloy may effect the mechanical properties of the metal or alloy.One of the heat treatment processes that can be applied to metal or alloy after welding is annealing process.Annealing proces is a process of heat treatment of metal or alloy by heating the metal at a certain temperature,holding at that temperature for a while and cooling the metal with a very slow cooling rate. The process of heattreatment provided aims to improve the mechanical properties of metal or alloys. Based on the above, this research is aimed to find out the influence of St 42 steel after welding and to experience annealing process to the hardness and the resulting microstructure. This research is an experimental research. The materials used are St 42 steel, given welding treatment then in annealing process on temperature variation 500C, 6000C and 700C with holding time I hour. Furthermore, violent testing and microstructural observations are followed The result of dataanalysis shows that the highest mean hardness value at annealing temperafure is 5000C ie 170,03 HVN. While at annealing temperature 7000 C has the lowest mean value of hardness is 125,13 MVN.